NANOEMULSION GEL OF NUTRACEUTICAL CO-ENZYME Q10 AS AN ALTERNATIVE TO CONVENTIONAL TOPICAL DELIVERY SYSTEM TO ENHANCE SKIN PERMEABILITY AND ANTI-WRINKLE EFFICIENCY - El- Leithy, Eman S.; Makky, Amna M.; Khattab, Abeer M.; Hussein, Doaa G. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The object of our investigation was to develop and characterize nanoemulsion gel (NEG) as transdermal delivery systems for the poorly water soluble drug, Co-enzyme Q10 (CoQ10), to improve its solubility and skin permeability and thus improving its anti-wrinkle efficiency. Methods: An optimized nanoemulsion (NE) formula was chosen according to its particle size and stability and converted into nanoemulsion gel using different gelling agents, including; carbopol 934 (1%), xanthan gum (2%) and sodium carboxymethyl cellulose(NaCMC) (2%). Drug loaded nanoemulsion gels were characterized for particle size, zeta potential, viscosity and rheological behavior, conductivity, spreadability, drug content and permeation studies using Franz diffusion cell. Results: NEG containing 10% w/v isopropyl myristate (IPM) as oil, 60% w/v tween 80 and transcutol HP as surfactant/co-surfactant mixture (S/CoS), 30%w/v water, 2%w/v drug, and 1% w/v carbopol 934 as gelling gent was concluded as an optimized NEG formula. It exhibited pH, viscosity, drug content, particle size, zeta potential, polydispersity index(PDI) and spreadability, as 5.4±0.011, 27588±2034.34 cps,101.51±0.93%,120.5±1.19 nm,-29.8±1.46, 0.273 and 6.16±0.28 cm, respectively. Also, it showed significantly higher cumulative amount of drug permeated through dialysis membrane (281.71±0.97μg/cm2) and through rat skin (20.73±2.5 μg/cm2) than the other formulae and marketed formulation (P<0.001). In addition, its permeability parameters like drug flux (Jss), enhancement ratio (Er) and permeability coefficient (Kp) exhibited the highest values; 12.79µg/cm2/h, 95.92×10-4 cm2/h and 57.35, respectively for in vitro permeation study and 0.968µg/cm2/h, 7.26×10-4 cm2/h and 1.183, respectively for ex-vivo permeation study. Further histopathological evaluation test showed that CoQ10 NEG has a good anti-wrinkle efficacy compared to the conventional topical dosage form. Conclusion: These results judged NEG to be a promising alternative carrier for topical delivery of CoQ10 to enhance its solubility, skin permeability and thus anti-wrinkle efficiency.